2002
DOI: 10.1042/cs1040017
|View full text |Cite
|
Sign up to set email alerts
|

(Ab)normal saline and physiological Hartmann's solution: a randomized double-blind crossover study

Abstract: In this double-blind crossover study, the effects of bolus infusions of 0.9% saline (NaCl) and Hartmann's solution on serum albumin, haematocrit and serum and urinary biochemistry were compared in healthy subjects. Nine young adult male volunteers received 2-litre intravenous infusions of 0.9% saline and Hartmann's solution on separate occasions, in random order, each over 1 h. Body weight, haematocrit and serum biochemistry were measured pre-infusion and at 1 h intervals for 6 h. Biochemical analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(74 citation statements)
references
References 29 publications
3
68
2
1
Order By: Relevance
“…It increased after both infusions, which is contrary to our study hypothesis, and also contrary to previous findings of a reduction of 10-15% after saline [2,4]. Although our study confirmed that the urine output was lower with isotonic saline compared with the buffered Ringer's solution [3,17,18], the difference was more dependent on pre-infusion fluid retention than on the choice of fluid. Patients with fluid retention excreted three times more fluid when receiving Ringer's acetate compared with saline (Table 2), while there was virtually no increase in urine flow in response to isotonic saline.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…It increased after both infusions, which is contrary to our study hypothesis, and also contrary to previous findings of a reduction of 10-15% after saline [2,4]. Although our study confirmed that the urine output was lower with isotonic saline compared with the buffered Ringer's solution [3,17,18], the difference was more dependent on pre-infusion fluid retention than on the choice of fluid. Patients with fluid retention excreted three times more fluid when receiving Ringer's acetate compared with saline (Table 2), while there was virtually no increase in urine flow in response to isotonic saline.…”
Section: Discussioncontrasting
confidence: 57%
“…Isotonic saline is the most widely used infusion fluid in Europe [16], despite reports of potential harm [3,[5][6][7]17]. These warnings are not supported by the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…Such changes, in line with the recently published UK guidance (1) , appear to yield considerable clinical benefit as judged by our pragmatic study, and these benefits are in line with those previously reported from formal clinical trials (3,4) . Our data underline the need for continuous audit of clinical practice with appropriate analysis to determine the likely impacts of change and show that relatively simple, low-cost, pragmatic methodologies can be used to assess changes in clinical practice.…”
Section: Discussionsupporting
confidence: 90%
“…It has been theorized that the formation of endomysial edema, and an associated increase in diffusion distance from blood vessel to muscle fibers, may contribute to muscle fiber damage in patients with septic shock (38). In observational and experimental models, hyperchloremia or chloride-rich fluids have been associated with fluid retention, reduced renal perfusion, AKI, and mortality (39)(40)(41)(42)(43)(44). If any of these effects on biological systems are clinically significant, it is plausible that one or a ORIGINAL RESEARCH combination of volume-related complications could result in a prolonged hospital stay, impaired mobility, and/or need for discharge to a healthcare facility.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%